Longitudinal cognitive decline in the AIBL cohort: the role of APOE ε4 status - Foster, J.; Albrecht, Matthew; Szoeke, C.; Maruff, P.; Savage, G.; Lautenschlager, N.; Ellis, K.; Taddei, K.; Martins, R.; Masters, C.; Ames, D. (Elsevier, 2014)
The ε4 polymorphism of the APOE gene confers a substantially increased risk of developing Alzheimer's disease (AD). However, the influence of the ε4 allele on cognitive functioning in ageing individuals is more contentious. Previously, we demonstrated relatively little evidence for a role of the ε4 allele on baseline cognitive performance in older adults in the Australian Imaging, Biomarkers and Lifestyle (AIBL) Study of Ageing (Foster et al [2013], BRAIN, 136, 2201-16). We here investigated whether the APOE ε4 allele influenced cognitive status over time when the AIBL cohort was followed longitudinally over a 3-year period.